The Effectiveness of a Low Glycemic Index/Load Diet on Cardiometabolic, Glucometabolic, and Anthropometric Indices in Children with Overweight or Obesity: A Systematic Review and Meta-Analysis - Ioustini Kalaitzopoulou; Xenophon Theodoridis; Evangelia Kotzakioulafi; Kleo Evripidou; Michail Chourdakis (MDPI AG, 2023)
(1) Background: This systematic review and meta-analysis aims to evaluate the impact of a low glycemic index (LGI) and low glycemic load (LGL) diet on children with overweight and obesity, analyzing any changes in anthropometric, cardiometabolic, and glucometabolic parameters. (2) Methods: Three electronic databases (PubMed, Scopus, CENTRAL), as well as clinical trial registries and reference lists of the included studies, were searched for eligible randomized control trials (RCTs). Two independent reviewers performed the screening of the studies, data extraction, and risk of bias assessment. Mean difference (MD) and 95% confidence intervals (CI) using a random effects model were calculated for each outcome. (3) Results: Eleven RCTs (n = 634) examining the effect of LGI diet versus control were identified. The synthesized data provided from the RCTs indicate no difference between intervention and control groups regarding primary outcomes (body weight (MD: −0.14; 95% CI −1.93 to 1.64, 5 trials), body mass index (BMI) (MD: −0.31; 95% CI −0.85 to 0.23, 6 trials), BMI z-score (MD: −0.03; 95% CI −0.09 to 0.02, 5 trials), and waist circumference (MD: −0.52; 95% CI −2.35 to 1.31, 5 trials)) and other measures of cardiometabolic and glucometabolic parameters. The majority of trials were classified as "some concerns". (4) Conclusions: LGI and LGL diets do not seem to be associated with changes in adiposity, cardiometabolic or glucometabolic markers in children with overweight or obesity. Further research comparing the LGI diet to a high glycemic index diet, with proper methodological standards, is required to clarify the benefits of a LGI diet in this population.